Making Sense of the Alt-Right - Hawley, George (New York, NY : Columbia University Press, 2018)
During the 2016 election, a new term entered the mainstream American political lexicon: alt-right, short for alternative right. Despite the innocuous name, the alt-right is a white-nationalist movement. Yet it differs from earlier racist groups: it is youthful and tech savvy, obsessed with provocation and trolling, amorphous, predominantly online, and mostly anonymous. And it was energized by Donald Trump s presidential campaign. In Making Sense of the Alt-Right, George Hawley provides an accessible introduction and gives vital perspective on the emergence of a group whose overt racism has confounded expectations for a more tolerant America.Hawley explains the movement s origins, evolution, methods, and core belief in white-identity politics. The book explores how the alt-right differs from traditional white nationalism, libertarianism, and other online illiberal ideologies such as neoreaction, as well as from mainstream Republicans and even Donald Trump and Steve Bannon. The alt-right s use of offensive humor and its trolling-driven approach, based in animosity to so-called political correctness, can make it difficult to determine true motivations. Yet through exclusive interviews and a careful study of the alt-right s influential texts, Hawley is able to paint a full picture of a movement that not only disagrees with liberalism but also fundamentally rejects most of the tenets of American conservatism. Hawley points to the alt-right s growing influence and makes a case for coming to a precise understanding of its beliefs without sensationalism or downplaying the movement s radicalism.
Frontmatter -- Contents -- Acknowledgments -- Introduction -- 1. The Alt-Right s Goals and Predecessors -- 2. The First Wave of the Alt-Right -- 3. The Alt-Right Returns -- 4. The Alt-Right Attack on the Conservative Movement -- 5. The Alt-Right and the 2016 Election -- 6. The Alt-Lite -- Conclusion -- Notes -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Sep 2018)
Keywords: White nationalism -- United States -- History -- 21st century; White supremacy movements -- United States -- History -- 21st century; Whites -- United States -- Politics and government -- 21st century